A semi-solid battery based on lithium iron phosphate system and a preparation method thereof
Patent Information
- Application Number
- CN202611181784.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-23
AI Technical Summary
传统液态锂离子电池虽然技术成熟,但存在电解液泄漏、易燃易爆等安全隐患,且能量密度提升空间有限
[0032]1.在正极片和负极片的表面设置界面导电层,界面导电层中的氮化锂具有独特的六角形晶体结构,使其与电解质界面之间具有更好的界面接触效果,降低界面势垒,促进锂离子均匀传输。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application relates to the technical field of semi-solid batteries, and in particular to a semi-solid battery based on a lithium iron phosphate system and its preparation method. Background Technology
[0002] With the rapid development of new energy vehicles and energy storage, higher demands are being placed on the energy density, safety, and cycle life of batteries. While traditional liquid lithium-ion batteries are technologically mature, they pose safety hazards such as electrolyte leakage and flammability / explosion, and their energy density improvement potential is limited. All-solid-state batteries, although offering high safety and significant energy density potential, currently face challenges such as high interfacial impedance, complex manufacturing processes, and high costs, making large-scale commercial application difficult in the short term.
[0003] Lithium iron phosphate (LiFePO4) is widely used in the field of lithium-ion batteries as a cheap, stable and safe cathode material. However, traditional lithium iron phosphate batteries have problems such as low electronic conductivity and low ion diffusion coefficient, which limit their performance improvement.
[0004] Currently, the electrolytes of conventional semi-solid batteries are mostly in a gel state. Batteries made with gel electrolytes have poor electrical performance, mainly because the interface contact between gel electrolytes and lithium iron phosphate cathodes and graphite anodes is poor, and micro-gaps are prone to exist, which leads to obstacles in ion transport paths during charging and discharging, resulting in poor rate performance and rapid performance decay during cycling. Summary of the Invention
[0005] In order to obtain a semi-solid battery with good rate performance and high cycle stability, this application provides a semi-solid battery based on lithium iron phosphate system and its preparation method.
[0006] Firstly, the semi-solid-state battery based on the lithium iron phosphate system provided in this application adopts the following technical solution:
[0007] A semi-solid-state battery based on lithium iron phosphate system includes a cell and an electrolyte. The cell includes a positive electrode and a negative electrode. An interface conductive layer is provided on the surface of both the positive electrode and the negative electrode. The interface conductive layer is made of a conductive paste, which includes 0.2-0.5 parts by weight of modified lithium nitride, 0.02-0.05 parts by weight of binder, and 3-5 parts by weight of anhydrous ethanol.
[0008] The modified lithium nitride is coated with a nano-alumina layer, and the modified lithium nitride is prepared by the following steps:
[0009] Nano-alumina was dispersed in anhydrous ethanol and ultrasonicated until uniformly dispersed. Lithium nitride and nano-alumina were ball-milled for 3-5 hours under an inert atmosphere at a mass ratio of (8-10):1. The ball-milled mixture was then dried to obtain modified lithium nitride.
[0010] The electrolyte is formed by reacting lithium salt, solvent, additive, monomer, crosslinking agent and liquid initiator, and the mass ratio of lithium salt, solvent, additive, monomer, crosslinking agent and liquid initiator is (6-18):(75-90):(1-5):(5-10):(1-1.5):(0.3-0.6).
[0011] By adopting the above technical solution, an interfacial conductive layer is formed on the surface of the positive and negative electrode sheets. The lithium nitride in the interfacial conductive layer has a unique hexagonal crystal structure, which improves the interfacial contact between the lithium nitride and the electrolyte interface, reduces the interfacial barrier, and promotes uniform lithium ion transport. Since lithium nitride is easily hydrolyzed, it is modified to coat its surface with an aluminum oxide coating layer. This coating layer is formed on the surface of the lithium nitride through physical adsorption or chemical bonding, preventing it from contacting water and oxygen, while simultaneously optimizing interfacial ion conduction.
[0012] A gel electrolyte is formed by polymerizing lithium salt, solvent, additives, monomers, crosslinking agents, and liquid initiators to form an electrolyte solution at a thermal initiation temperature. This gel electrolyte possesses a relatively uniform internal structure, facilitating lithium-ion transport and exhibiting good structural stability at high temperatures. It can adapt to the volume changes of the lithium iron phosphate electrode during charging and discharging, is less prone to interface separation, and ensures the rate performance and cycle stability of the semi-solid-state battery. There are no significant differences when the mass ratio of lithium salt, solvent, additives, monomers, crosslinking agents, and liquid initiators is within the range of (6-18):(75-90):(1-5):(5-10):(1-1.5):(0.3-0.6).
[0013] Optionally, the surface of the modified lithium nitride is further coated with a solid initiator, which is prepared by the following steps:
[0014] Nano-alumina was dispersed in anhydrous ethanol and ultrasonicated until uniformly dispersed. Lithium nitride and nano-alumina were ball-milled for 3-5 hours under an inert atmosphere at a mass ratio of (8-10):1. A solid initiator was then added and ball-milled again. The mass ratio of the solid initiator to nano-alumina was (0.03-0.2):1. The ball-milled mixture was dried to obtain modified lithium nitride.
[0015] Optionally, the solid initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide.
[0016] By adopting the above technical solution, since the solid initiator is a solid powder, when it is directly added to the battery cell along with other raw materials of the electrolyte, it is easy to cause uneven distribution of the initiator in the electrolyte system, which in turn affects the uniformity of polymerization and causes poor ion transport pathways. By adding the solid initiator during the preparation of modified lithium nitride, it coats the surface of lithium nitride, isolating it from water and oxygen, thus preventing the hydrolysis of lithium nitride. In addition, it can also make the solid initiator uniformly distributed in the interfacial conductive layer on the positive and negative electrode surfaces. When the monomers in the electrolyte undergo thermally initiated polymerization to form a gel electrolyte, the solid initiator in the interfacial conductive layer can react with the monomers in the electrolyte to form a film, which enhances the interfacial contact effect and further improves thermal stability, enabling the semi-solid battery to have good rate performance and cycle stability even in high-temperature environments.
[0017] Optionally, the modified lithium nitride is obtained by freeze drying at a temperature of -30°C to -50°C for 10-12 hours.
[0018] By employing the above-mentioned technical solution, the modified lithium nitride prepared by freeze-drying, when applied to the interfacial conductive layer, exhibits enhanced interfacial stability, which helps improve the cycle stability and rate performance of semi-solid-state batteries. This is because freeze-drying helps retain the active sites of nano-alumina, and the porous structure formed after freeze-drying promotes rapid lithium-ion transport and reduces polarization effects, thereby improving high-rate charge-discharge capabilities. Furthermore, freeze-dried modified lithium nitride further facilitates the uniform release of solid-state initiators during the thermally initiated polymerization process of the electrolyte, forming a more uniformly polymerized gel electrolyte, promoting lithium-ion transport, and reducing interfacial impedance.
[0019] Optionally, the lithium salt includes one or more of lithium hexafluorophosphate, lithium difluorophosphate, lithium nitrate, and lithium tetrafluoroborate;
[0020] The solvent includes one or more of ethylene carbonate, propylene carbonate, ethyl acetate, and methyl ethyl carbonate.
[0021] Optionally, the additive comprises diphenyl sulfone and vinylene carbonate in a mass ratio of (0.6-1):1.
[0022] By employing the above technical solution, diphenyl sulfone is compounded with vinylene carbonate, allowing diphenyl sulfone to dissolve well in the vinylene carbonate and be added to the electrolyte as an additive. Due to the rigid planar structure of diphenyl sulfone, it can form a cross-linked network with monomers in the electrolyte through physical entanglement or chemical bonding during polymerization. The supporting effect of its rigid skeleton can significantly improve the mechanical toughness of the gel electrolyte and enhance its stability at high temperatures. In addition, the sulfur content in the additive can reduce the oxidative decomposition of the electrolyte under high-temperature conditions through mechanisms such as sulfur redox mediation and optimization of the electrolyte chemical environment, thereby improving the battery's antioxidant performance and cycle stability. It has antioxidant properties and can also improve the thermal stability of the electrolyte, reducing performance degradation caused by high-temperature environments.
[0023] Optionally, the monomer includes one or more of methyl methacrylate, butyl methacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, and dipentaerythritol hexaacrylate;
[0024] The crosslinking agent includes one or more of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and polyether acrylate;
[0025] The liquid initiator includes one or more of benzoyl tert-butyl peroxide and methyl ethyl ketone peroxide.
[0026] Secondly, this application provides a method for preparing a semi-solid-state battery based on a lithium iron phosphate system, employing the following technical solution:
[0027] A method for preparing a semi-solid-state battery based on lithium iron phosphate includes the following steps:
[0028] (1) The conductive paste is coated on the surface of the positive electrode and the negative electrode, and after drying, a conductive interface layer is formed with a thickness of 1μm-5μm;
[0029] (2) The positive and negative electrode sheets with conductive interface layers are made into a battery cell;
[0030] (3) After injecting electrolyte into the cell, seal and age it, raise the temperature to 40℃-80℃ and keep it for 20h-40h, then cool it down and let it stand to obtain a semi-solid battery.
[0031] In summary, this application includes at least one of the following beneficial technical effects:
[0032] 1. An interfacial conductive layer is set on the surface of the positive and negative electrode plates. The lithium nitride in the interfacial conductive layer has a unique hexagonal crystal structure, which makes it have a better interfacial contact effect with the electrolyte interface, reduces the interfacial barrier, and promotes uniform lithium ion transport.
[0033] 2. By adding solid initiators during the preparation of modified lithium nitride, they are coated on the surface of lithium nitride, isolating it from water and oxygen, thus preventing the hydrolysis of lithium nitride. In addition, the solid initiators can be uniformly distributed in the interfacial conductive layer on the positive and negative electrode surfaces. When the monomers in the electrolyte undergo thermally initiated polymerization to form a gel electrolyte, the solid initiators in the interfacial conductive layer can react with the monomers in the electrolyte to form a film, enhancing the interfacial contact effect and further improving thermal stability. This allows the semi-solid battery to have good rate performance and cycle stability even at high temperatures.
[0034] 3. When freeze-dried modified lithium nitride is applied to the interfacial conductive layer, it enhances interfacial stability, which helps improve the cycle stability and rate performance of semi-solid-state batteries. This is because freeze-drying helps retain the active sites of nano-alumina, and the porous structure formed after freeze-drying promotes rapid lithium-ion transport and reduces polarization effects, thereby improving high-rate charge-discharge capabilities. Furthermore, freeze-dried modified lithium nitride further promotes the uniform release of solid-state initiators during the thermal polymerization process of the electrolyte, forming a more uniform gel electrolyte, promoting lithium-ion transport, and reducing interfacial impedance. Detailed Implementation
[0035] Source of raw materials
[0036] The average particle size of the nano-alumina is 30-60 nm, and the CAS number is 1344-28-1.
[0037] Lithium nitride CAS number: 26134-62-3, particle size range 200-300nm;
[0038] The monomers such as methyl methacrylate, butyl methacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, and dipentaerythritol hexaacrylate, as well as the crosslinking agents such as polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, pentaerythritol triacrylate, and pentaerythritol tetraacrylate, the liquid initiators such as benzoyl tert-butyl peroxide and methyl ethyl ketone peroxide, the solvents such as ethylene carbonate, propylene carbonate, ethyl acetate, and methyl ethyl carbonate, and the lithium salts such as lithium hexafluorophosphate, lithium difluorophosphate, lithium nitrate, and lithium tetrafluoroborate, and the solid initiators such as azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide in the embodiments of this application are all commercially available.
[0039] Preparation Example
[0040] Preparation Examples 1-3
[0041] A conductive paste comprises 0.2-0.5 kg of modified lithium nitride, 0.02-0.05 kg of binder, and 3-5 kg of anhydrous ethanol. The specific amounts of raw materials are shown in Table 1.
[0042] The adhesive is a styrene-butadiene rubber adhesive.
[0043] The modified lithium nitride is lithium nitride with a nano-alumina coating on its surface, and its preparation method is as follows:
[0044] Nano-alumina was dispersed in anhydrous ethanol at a concentration of 5 wt% and ultrasonicated until uniformly dispersed. Lithium nitride and nano-alumina were ball-milled at a mass ratio of 9:1 for 4 hours under a nitrogen atmosphere. The ball-milled mixture was then freeze-dried at a temperature of -50℃ for 10 hours to obtain modified lithium nitride.
[0045] Table 1. Raw material consumption for preparing conductive pastes in Examples 1-3 (unit: kg)
[0046]
[0047] Preparation Example 4
[0048] A conductive paste, differing from Preparation Example 2 in that the modified lithium nitride is lithium nitride with a surface coated with a solid initiator and a nano-alumina coating, the solid initiator being azobisisobutyronitrile (AIBN), and its preparation method is as follows:
[0049] Nano-alumina was dispersed in anhydrous ethanol at a concentration of 5 wt% and ultrasonicated until uniformly dispersed. Lithium nitride and nano-alumina were ball-milled for 2 hours at a mass ratio of 9:1 under a nitrogen atmosphere. Then, a solid initiator was added and ball-milled for another 2 hours. The mass ratio of solid initiator to nano-alumina was 0.1:1. The ball-milled mixture was freeze-dried at a temperature of -50℃ for 10 hours to obtain modified lithium nitride.
[0050] Preparation Example 5
[0051] A conductive paste, which differs from Preparation Example 4 in that an equal amount of benzoyl peroxide is used instead of azobisisobutyronitrile.
[0052] Comparative Preparation Example 1
[0053] A conductive paste, differing from Preparation Example 2 in that the modified lithium nitride is obtained by drying in a high-temperature drying oven, and its preparation method is as follows:
[0054] Nano-alumina was dispersed in anhydrous ethanol at a concentration of 5 wt% and ultrasonicated until uniformly dispersed. Lithium nitride and nano-alumina were ball-milled at a mass ratio of 9:1 for 4 hours under a nitrogen atmosphere. The ball-milled mixture was then dried at a high temperature of 80°C for 10 hours to obtain modified lithium nitride.
[0055] Comparative Preparation Example 2
[0056] A conductive paste, which differs from Preparation Example 2 in that an equal amount of unmodified lithium nitride is used to replace modified lithium nitride.
[0057] Example
[0058] Example 1
[0059] A semi-solid-state battery based on lithium iron phosphate system, including a cell and an electrolyte. The cell includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. The separator is a 6 μm polyimide film. An interface conductive layer is provided on the surface of both the positive electrode and the negative electrode. The interface conductive layer is made of the conductive paste of Preparation Example 1.
[0060] The electrolyte comprises a lithium salt, a solvent, additives, a monomer, a crosslinking agent, and a liquid initiator. The mass ratio of the lithium salt, solvent, additives, monomer, crosslinking agent, and liquid initiator is 6:75:1:5:1:0.3. The lithium salt is lithium hexafluorophosphate, the solvent is ethylene carbonate, the additives are diphenyl sulfone and vinylene carbonate in a mass ratio of 0.6:1, the monomer is methyl methacrylate, the crosslinking agent is polyethylene glycol diacrylate, and the liquid initiator is benzoyl tert-butyl peroxide.
[0061] A method for preparing a semi-solid-state battery based on lithium iron phosphate includes the following steps:
[0062] (1) Preparation of positive electrode sheet: Lithium iron phosphate active material, carbon black conductive agent, polyvinylidene fluoride binder and N-methyl-2-pyrrolidone solvent are mixed in a mass ratio of 90:2.5:2.5:5 to prepare positive electrode slurry. The positive electrode slurry is coated on aluminum foil current collector, dried and wound at 120°C, and then rolled and sliced to form positive electrode sheet.
[0063] (2) Preparation of negative electrode sheet: graphite active material, carbon black conductive agent and polyvinylidene fluoride binder are mixed in a mass ratio of 95:3:2 to prepare negative electrode slurry. The negative electrode slurry is coated on copper foil current collector, dried at 105°C, and then rolled and sliced to obtain negative electrode sheet.
[0064] (3) Preparation of the interface conductive layer: The conductive paste of Preparation Example 1 was coated on the surface of the positive electrode and the negative electrode respectively, and after drying, a conductive interface layer with a thickness of 3 μm was formed;
[0065] (4) Cell preparation: The positive electrode, negative electrode and separator with conductive interface layer are wound into a cell with a capacity of 10Ah;
[0066] (5) Preparation of electrolyte: First, mix the monomer and crosslinking agent, then add them to the solvent, and finally add lithium salt and additives and mix thoroughly to obtain electrolyte.
[0067] (6) Preparation of semi-solid battery: After injecting electrolyte into the cell, seal and age it, raise the temperature to 65°C and keep it for 25 hours to allow the electrolyte in the cell to undergo thermal polymerization to form a gel electrolyte. Cool down to 40°C and let it stand to finally obtain a semi-solid battery.
[0068] Examples 2-5
[0069] A semi-solid-state battery based on lithium iron phosphate system, which differs from Example 1 in that the conductive slurry is prepared sequentially from Preparation Examples 2-5.
[0070] Example 6
[0071] A semi-solid-state battery based on a lithium iron phosphate system differs from Example 1 in that the electrolyte comprises a lithium salt, a solvent, additives, a monomer, a crosslinking agent, and a liquid initiator in a mass ratio of 13:80:3:8:1.3:0.4. The lithium salt is lithium difluorophosphate, the solvent is propylene carbonate, the additives are diphenyl sulfone and vinylene carbonate in a mass ratio of 0.8:1, the monomer is propylene carbonate, the crosslinking agent is polyethylene glycol dimethacrylate, and the liquid initiator is methyl ethyl ketone peroxide. All other components are the same.
[0072] Example 7
[0073] A semi-solid-state battery based on a lithium iron phosphate system differs from Example 1 in that the electrolyte comprises a lithium salt, a solvent, additives, a monomer, a crosslinking agent, and a liquid initiator in a mass ratio of 18:90:5:10:1.5:0.6. The lithium salt is lithium tetrafluoroborate, the solvent is ethyl acetate, the additives are diphenyl sulfone and vinylene carbonate in a mass ratio of 1:1, the monomer is pentaerythritol triacrylate, the crosslinking agent is polyether acrylate, and the liquid initiator is methyl ethyl ketone peroxide.
[0074] Comparative Example 1 - Comparative Example 2
[0075] A semi-solid-state battery based on lithium iron phosphate system, which differs from Example 1 in that the conductive slurry is prepared sequentially from Comparative Preparation Example 1 to Comparative Preparation Example 2.
[0076] Comparative Example 3
[0077] A conductive paste, which differs from Example 1 in that an equal amount of azobisisobutyronitrile solid initiator is used instead of the liquid initiator tert-butyl peroxide.
[0078] Comparative Example 4
[0079] A semi-solid-state battery based on lithium iron phosphate system differs from Example 1 in that the positive and negative electrode surfaces are not provided with an interface conductive layer, that is, the preparation method does not include the step of preparing an interface conductive layer.
[0080] Performance testing
[0081] 1. Capacity retention rate:
[0082] Capacity retention rate tests were conducted at ambient temperature (25℃) and high temperature (55℃). Test conditions: charging at a rate of 1.0C and discharging at a rate of 1.0C, with a voltage range of 2.0-3.65V. After 100 and 300 cycles under the above conditions, the capacity retention rate was calculated. For example, the capacity retention rate after 100 cycles = specific capacity after the 100th discharge cycle / specific capacity after the first discharge cycle * 100%.
[0083] The capacity retention rate of the semi-solid-state batteries in Examples 1-7 and Comparative Examples 1-3 was tested, and the test results are shown in Table 2.
[0084] Table 2 Test results of Examples 1-7 and Comparative Examples 1-3
[0085]
[0086] Combining the preparation examples 1-3 and Examples 1-3 with the test results in Table 2, it can be seen that when the conductive interface layer made from the conductive paste of Preparation Examples 1-3 is placed on both the positive and negative electrode plates, it exhibits good rate performance and cycle stability under both room temperature and high temperature environments. Among them, the conductive paste of Preparation Example 2 is the superior preparation example. The reason for this is that lithium nitride in the interface conductive layer has a unique hexagonal crystal structure, which allows for better interfacial contact with the electrolyte interface, reduces the interfacial barrier, and promotes uniform lithium-ion transport.
[0087] Combining Examples 2 and 4-5 with the test results in Table 2, it can be seen that Examples 4-5 are superior to Example 2. The reason for this is that by adding the solid initiator during the preparation of modified lithium nitride in the conductive slurry of Examples 4-5, the solid initiator is coated on the surface of lithium nitride, isolating it from water and oxygen, thus preventing the hydrolysis of lithium nitride. In addition, it can also make the solid initiator uniformly distributed in the interfacial conductive layer on the positive and negative electrode surfaces. When the monomers in the electrolyte undergo thermally initiated polymerization to form a gel electrolyte, the solid initiator in the interfacial conductive layer can react with the monomers in the electrolyte to form a film, which enhances the interfacial contact effect and further improves the thermal stability, so that the semi-solid battery can also have good rate performance and cycle stability in high-temperature environments.
[0088] Combining the test results of Examples 1 and 6-7 with those in Table 2, it can be seen that there is no significant substantial difference between the test results of Examples 1 and 6-7. This indicates that the gel electrolyte formed by the polymerization reaction of lithium salt, solvent, additives, monomers, crosslinking agents, and liquid initiators in this application has a relatively uniform internal structure, which facilitates lithium-ion transport and exhibits good structural stability at high temperatures. It can adapt to the volume changes of the lithium iron phosphate electrode during charging and discharging, is less prone to interface separation, and ensures the rate performance and cycle stability of the semi-solid-state battery. By compounding diphenyl sulfone with vinylene carbonate, diphenyl sulfone is well dissolved in vinylene carbonate and added to the electrolyte as an additive. Due to the rigid planar structure of diphenyl sulfone, it can form a cross-linked network with monomers in the electrolyte through physical entanglement or chemical bonding during polymerization. The supporting effect of its rigid skeleton can significantly improve the mechanical toughness of the gel electrolyte and enhance its stability at high temperatures. In addition, the sulfur content in the additive can reduce the oxidative decomposition of the electrolyte under high-temperature conditions through the redox-mediated effect of sulfur and the optimization of the electrolyte chemical environment, thereby improving the battery's antioxidant performance and cycle stability. It has antioxidant properties and can also improve the thermal stability of the electrolyte, reducing the performance degradation caused by high-temperature environments.
[0089] Combining the test results of Example 1 and Comparative Example 1 with those in Table 2, it can be seen that Example 1 is superior to Comparative Example 1. The reason for this is that when the modified lithium nitride prepared by freeze-drying is applied to the interfacial conductive layer, the interfacial stability is enhanced, which helps to improve the cycle stability and rate performance of the semi-solid-state battery. This is because freeze-drying helps to retain the active sites of nano-alumina, and the porous structure formed after freeze-drying can promote the rapid transport of lithium ions and reduce polarization effects, thereby improving the high-rate charge-discharge capability. In addition, the freeze-dried modified lithium nitride is more conducive to promoting the uniform release of solid initiators during the thermal initiation polymerization process of the electrolyte, forming a more uniformly polymerized gel electrolyte, promoting lithium ion transport, and reducing interfacial impedance.
[0090] Combining Example 1 and Comparative Example 2 with Table 2, it can be seen that Example 1 is superior to Comparative Example 2. The reason may be that lithium nitride is easily hydrolyzed. Therefore, lithium nitride is modified to have an aluminum oxide coating on its surface. This allows a protective layer to be formed on the surface of lithium nitride through physical adsorption or chemical bonding, preventing it from contacting water and oxygen, while also optimizing interfacial ion conduction.
[0091] Combining the test results of Example 1 and Comparative Example 3 with Table 2, it can be seen that Example 1 is superior to Comparative Example 3. The reason for this is that, since the solid initiator is a solid powder, when it is added directly to the cell along with other raw materials of the electrolyte, it is easy to cause uneven distribution of the initiator in the electrolyte system, which affects the uniformity of polymerization and causes poor ion transport path. As a result, the semi-solid battery of Comparative Example 3 cannot guarantee its rate performance and cycle stability.
[0092] Combining the results of Example 1 and Comparative Example 4 with the test results in Table 2, it can be seen that Example 1 is superior to Comparative Example 4. The reason for this is that the interface contact between the gel electrolyte and the lithium iron phosphate positive electrode and the graphite negative electrode is poor, and micro-gaps are prone to exist, which leads to obstacles in the ion transport path during charging and discharging, resulting in poor rate performance and rapid performance decay during cycling. Therefore, this application sets an interface conductive layer on the surface of the positive and negative electrode sheets. The lithium nitride in the interface conductive layer has a unique hexagonal crystal structure, which makes it have a better interface contact effect with the electrolyte interface, reduces the interface barrier, and promotes uniform lithium ion transport.
[0093] The above are all preferred embodiments of this application, and are not intended to limit the scope of protection of this application. Therefore, all equivalent changes made in accordance with the structure, shape and principle of this application should be covered within the scope of protection of this application.
Claims
1. A semi-solid-state battery based on a lithium iron phosphate system, comprising a cell and an electrolyte, wherein the cell comprises a positive electrode and a negative electrode, characterized in that: Both the positive and negative electrode plates have an interface conductive layer on their surfaces. The interface conductive layer is made of a conductive paste, which includes 0.2-0.5 parts by weight of modified lithium nitride, 0.02-0.05 parts by weight of binder, and 3-5 parts by weight of anhydrous ethanol. The modified lithium nitride is coated with a nano-alumina layer, and the modified lithium nitride is prepared by the following steps: Nano-alumina was dispersed in anhydrous ethanol and ultrasonicated until uniformly dispersed. Lithium nitride and nano-alumina were ball-milled for 3-5 hours under an inert atmosphere at a mass ratio of (8-10):
1. The ball-milled mixture was then dried to obtain modified lithium nitride. The electrolyte is formed by reacting lithium salt, solvent, additive, monomer, crosslinking agent and liquid initiator, and the mass ratio of lithium salt, solvent, additive, monomer, crosslinking agent and liquid initiator is (6-18):(75-90):(1-5):(5-10):(1-1.5):(0.3-0.6).
2. A semi-solid-state battery based on lithium iron phosphate system according to claim 1, characterized in that: The modified lithium nitride is also coated with a solid initiator. It is prepared by the following steps: Nano-alumina was dispersed in anhydrous ethanol and ultrasonicated until uniformly dispersed. Lithium nitride and nano-alumina were ball-milled for 3-5 hours under an inert atmosphere at a mass ratio of (8-10):
1. A solid initiator was then added and ball-milled again. The mass ratio of the solid initiator to nano-alumina was (0.03-0.2):
1. The ball-milled mixture was dried to obtain modified lithium nitride.
3. A semi-solid-state battery based on a lithium iron phosphate system according to claim 2, characterized in that: The solid initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide.
4. A semi-solid-state battery based on a lithium iron phosphate system according to claim 2, characterized in that: The modified lithium nitride was obtained by freeze drying at a temperature of -30℃ to -50℃ for 10-12 hours.
5. A semi-solid-state battery based on a lithium iron phosphate system according to claim 1, characterized in that: The lithium salt includes one or more of lithium hexafluorophosphate, lithium difluorophosphate, lithium nitrate, and lithium tetrafluoroborate; The solvent includes one or more of ethylene carbonate, propylene carbonate, ethyl acetate, and methyl ethyl carbonate.
6. A semi-solid-state battery based on a lithium iron phosphate system according to claim 1, characterized in that: The additives include diphenyl sulfone and vinylene carbonate in a mass ratio of (0.6-1):
1.
7. A semi-solid-state battery based on a lithium iron phosphate system according to claim 1, characterized in that: The monomers include one or more of methyl methacrylate, butyl methacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, and dipentaerythritol hexaacrylate; The crosslinking agent includes one or more of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, pentaerythritol triacrylate, and pentaerythritol tetraacrylate; The liquid initiator includes one or more of benzoyl tert-butyl peroxide and methyl ethyl ketone peroxide.
8. A method for preparing a semi-solid-state battery based on the lithium iron phosphate system according to any one of claims 1-7, characterized in that: Includes the following steps: (1) The conductive paste is coated on the surface of the positive electrode and the negative electrode, and after drying, a conductive interface layer is formed with a thickness of 1μm-5μm; (2) The positive and negative electrode sheets with conductive interface layers are made into a battery cell; (3) After injecting electrolyte into the cell, seal and age it, raise the temperature to 40℃-80℃ and keep it for 20h-40h, then cool it down and let it stand to obtain a semi-solid battery.
